Serum Potassium and Angiographic Severity of Coronary Artery Disease in Non-ST Elevation Myocardial Infarction - Sultana, Maimuna; Rahman, Afzalur; Karmakar, Pradip Kumar; Islam, AKM Monwarul; Mamun, Al; Siddika, Khondaker Aisha; Anwar, Kazi Md Rubayet; Datta, Gokul Chandra; Debnath, Deb Dulal; Chowdhury, Shaikat; Islam, Md Nazmul (Bangladesh Heart Journal, 2021)
Background: Non-ST elevation myocardial infarction (NSTEMI) patients like other patients with acute coronary syndrome (ACS) need assessment of severity of coronary artery disease (CAD) for prognostication and management. The available scoring systems are complex and include invasive parameters. On the other hand, potassium is a key element and its blood level has been shown to reflect health and disease of vasculature including in some ACS. Objective: The study was conducted to find out the relationship between serum potassium level and angiographic severity of CAD in NSTEMI. Method: A total of 200 cases of NSTEMI patients undergoing coronary angiography (CAG) were included. Patients getting medications that alter potassium homeostasis (e.g., diuretics, glucocorticoids, intravenous insulin), having renal impairment, haematological or liver disease, congenital or valvular heart disease, cardiomyopathy, prior percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) were excluded. Serum potassium was measured soon after admission with NSTEMI, and the patients were divided: mid to high normal (4 to 5.5 mmol/L) constituted the group I and low normal (3.5-3.9 mmol/L) constituted the group II. CAG was done during index admission, SYNTAX score calculated and compared between 2 groups. Results: High SYNTAX score was significantly more commonly found in group I than in group II (62.1% vs. 14.7%, p<0.001). Mean SYNTAX score was higher in group I than in group II (24.3±8.2 vs. 15.3±7.8, p<0.001). There was a linear relationship between serum potassium level and SYNTAX score. Mid to high normal serum potassium, hypertension and dyslipidemia were found to be significantly related to higher SYNTAX score with odds ratio being 10.44, 4.37 and 2.12 respectively. Conclusions: Within physiological limits, higher serum potassium level correlates with severe coronary artery disease in NSTEMI patients. It may be used as an additional tool in conjunction with other scoring systems to assess the severity of CAD in this subset of ACS patients. Bangladesh Heart Journal 2020; 35(2) : 128-133